2007
DOI: 10.1016/s0929-6646(07)60002-3
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of a Nosocomial Transmission of Tuberculosis at a District General Hospital

Abstract: Thorough collection along with molecular diagnosis and genotyping of all M. tuberculosis isolates are recommended for the confirmation of any suspected nosocomial TB outbreak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The geospatial findings in the present study are consistent with molecular epidemiologic findings [5]–[9]. A large nosocomial TB outbreak in 2003 involving 66 health care workers at a district hospital in Taipei was traced to an index case who was hospitalized in February 2002 by matched DNA fingerprints [5].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The geospatial findings in the present study are consistent with molecular epidemiologic findings [5]–[9]. A large nosocomial TB outbreak in 2003 involving 66 health care workers at a district hospital in Taipei was traced to an index case who was hospitalized in February 2002 by matched DNA fingerprints [5].…”
Section: Discussionsupporting
confidence: 86%
“…A large nosocomial TB outbreak in 2003 involving 66 health care workers at a district hospital in Taipei was traced to an index case who was hospitalized in February 2002 by matched DNA fingerprints [5]. Mycobacterial interspersed repetitive-unit-variable-number tandem-repeat (MIRU-VNTR) typing and spoligotyping was performed on TB isolates from 365 patients treated at a hospital in Taipei from 2002–2004; these results showed that 236 (65%) were clustered by genotype [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports of nosocomial TB outbreaks in Taipei, caused by delays in diagnosis and treatment [ 8 , 9 ], suggest that institutionalized TB reporting and DOTS alone may be insufficient to achieve targets established by Stop TB. In particular, previous studies have shown that TB diagnosis can be very complicated in hospitals, and delayed diagnosis is most likely to occur for hospitalized patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%